γ-aminobutyric acid as a metabolite: Interpreting magnetic resonance spectroscopy experiments. - Myers,JF; Nutt,DJ; Lingford-Hughes,AR (Journal of Psychopharmacology, 2016)
The current rise in the prevalence of magnetic resonance spectroscopy experiments to measure γ-aminobutyric acid in the living human brain is an exciting and productive area of research. As research spreads into clinical populations and cognitive research, it is important to fully understand the source of the magnetic resonance spectroscopy signal and apply appropriate interpretation to the results of the experiments. γ-aminobutyric acid is present in the brain not only as a neurotransmitter, but also in high intracellular concentrations, both as a transmitter precursor and a metabolite. γ-aminobutyric acid concentrations measured by magnetic resonance spectroscopy are not necessarily implicated in neurotransmission and therefore may reflect a very different brain activity to that commonly suggested. In this perspective, we examine some of the considerations to be taken in the interpretation of any γ-aminobutyric acid signal measured by magnetic resonance spectroscopy.